Therapeutic potential of targeting metabotropic glutamate receptors for Parkinson’s disease - Dickerson, Jonathan W (2012)
Parkinson’s disease (PD) is a progressive neurological disorder predominantly characterized by motor symptoms including bradykinesia and resting tremor. The gold standard of treatment for PD remains dopamine replacement therapy, which eventually fails due to continued progression of the disease and the development of debilitating side effects. Recent breakthroughs are providing the first major advances in the development of fundamentally new pharmacological strategies for the treatment of PD that do not rely on dopamine replacement strategies, but rather aim to reduce the overactive indirect pathway within the basal ganglia. In this article, we will review the role of metabotropic glutamate receptors within the basal ganglia and discuss the potential for modulation of metabotropic glutamate receptors as a treatment for PD.